2019
DOI: 10.3390/ijerph16101778
|View full text |Cite
|
Sign up to set email alerts
|

Dietary and Activity Factors Influence Poor Sleep and the Sleep-Obesity Nexus among Children

Abstract: Background: Behavioral factors such as physical activity, sedentary behavior and diet have previously been found to be key modifiable determinants of childhood overweight and obesity, yet require further investigation to provide an understanding of their potential influence on sleep outcomes along with the sleep-obesity nexus. Methods: The study included 2253 students (ages 8.8–13.5) from two monitoring studies across regional Victoria. Students completed a self-report electronic questionnaire on demographic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 73 publications
2
9
0
1
Order By: Relevance
“…This aligns with the research linking poor sleep quality with OWOB and an increased risk for cognitive and behavioral problems [56][57][58]. Research also links reduced sleep quality with high SSB intake, and in bed screen-time [59].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This aligns with the research linking poor sleep quality with OWOB and an increased risk for cognitive and behavioral problems [56][57][58]. Research also links reduced sleep quality with high SSB intake, and in bed screen-time [59].…”
Section: Discussionsupporting
confidence: 79%
“…These family stressors may also contribute to OWOB among children on Guam. With respect to OWOB prevention guidance, the study found evidence supporting previous studies' findings that traditional or low acculturation to be protective against obesity [39,59,60]. Healthy cultural behaviors, both unique to and shared across ethnic group(s), should be incorporated in future obesity interventions by highlighting healthy cultural values, practices and traditional foods.…”
Section: Discussionsupporting
confidence: 72%
“…Sedentary behaviors, such as increased screen time, related to higher levels of depression [ 47 , 53 ]. Increased screen time may also contribute to other health consequences such as suicidal ideation [50] , obesity [ 19 , 29 ], and changes to brain networks [40] . Furthermore, heavy screen users demonstrated the highest level of perceived stress and rated their health the lowest [43] .…”
Section: Introductionmentioning
confidence: 99%
“…Research studies conducted before the COVID-19 pandemic hypothesize that screen time may explain these results. For example, greater screen time has been related to decreased sleep quality [ 29 , 43 ] and decreased sleep quantity [43] . In children, screen time before bed negatively correlated with their sleep duration and contributed to later bedtimes compared to time spent with books before bed [6] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation